Bacillus cereus: an important foodborne pathogen - PEXARA (Α. ΠΕΞΑΡΑ), Α.; GOVARIS (A. ΓΚΟΒΑΡΗΣ), Α. (Journal of the Hellenic Veterinary Medical Society, 2018)
Β. cereus is a spore-forming bacterium, frequently found in the environment. Most of the strains can grow at a temperature range of 10° - 42° C. B. cereus grows under aerobic conditions, but anaerobic growth is, also, feasible. D1 2 1 values of the spores of B. cereus strains are usually in the range of 0.03 to 2.35 min. The pathogen produces at least five different enterotoxins (HBL, Nhe, CytK, BceT and FM) and one emetic toxin. The enterotoxins HBL, Nhe and CytK are the etiological agents of the B. cereus diarrhoeal disease. The enterotoxins are heat sensitive and can be inactivated by heating at 56° C for 5 min. They are, also, sensitive to low pH and proteolytic activity of enzymes and, subsequently, are inactivated in the acid environment of the stomach. B. cereus emetic toxin has been kept stable even in a heat treatment at 121° C for 2 h in in vitro tests. The emetic toxin is highly resistant to low pH (as low as 2) and to proteolysis. Thus, the emetic toxin cannot be inactivated in the acidic environment of the stomach and the enzyme proteolytic activity in the intestinal tract. B. cereus causes either a diarrhoeal or an emetic type of foodborne disease. The diarrhoeal disease is caused by the B. cereus enterotoxins, which are formed in the intestinal tract after the spores' germination and the subsequent growth of the vegetative cells. The symptoms are watery diarrhoea, abdominal cramps and pain. The emetic disease is caused by the ingestion of the preformed toxins in the foods. The symptoms are nausea and vomiting, occasionally followed by abdominal pain or diarrhoea. Foodborne outbreaks caused by B. cereus have been associated with various foods. The emetic disease has often been associated with the consumption of rice, pasta and other starchy foods, while the diarrheal disease is often linked to the consumption of dairy products, vegetables and meat. The most common food sources for B. cereus infections in humans are milk and dairy products. Among the reported foodborne outbreak cases in North America, Europe and Japan attributed to B. cereus represent a percentage of 1% to 22%. Most B. cereus foodborne cases were associated with the consumption of cooked foods that were cooled slowly and stored under improper refrigeration conditions. Foodborne diseases caused byB. cereus constitute a major problem in restaurants and catering services. Application of control measures, such as Good Manufacturing Practices (GMP) and Hazard Analysis Critical Control Points system (HACCP), in food processing lines can prevent contamination of the foods with pathogens like B. cereus.